1993
DOI: 10.2134/agronj1993.00021962008500030046x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Availability from Surface‐Applied and Soil‐Incorporated Crop Residues

Abstract: Management systems which maintain crop residues on the soil surface have prompted a need for more detailed information regarding crop residue N availability. Such information is needed from both agronomic and environmental standpoints. Our study examined the placement effects of 15N tagged alfalfa (Medicago sativa L.), sorghum [Sorghum bicolor (L.) Moench], and wheat (Triticum aestivum L.) residues on crop residue N availability in association with eight Oklahoma surface soils representing five soil orders. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…Fatores externos, como condições ambientais (Janzen & Radder, 1989;Stanford & Smith, 1972), tipo de solo (Ladd et al, 1981;Janns-Hammermeister et al, 1994) e forma de manejo (Wilson & Hargrove, 1986;Janzen & Radder, 1989), e inerentes aos adubos verdes (Palm & Sanchez, 1991;Smith & Sharpley, 1993), exercem grande influência sobre tais processos, devendo ser compreendidos e, na medida do possível, controlados para que otimizem os efeitos da adubação verde.…”
Section: Introductionunclassified
“…Fatores externos, como condições ambientais (Janzen & Radder, 1989;Stanford & Smith, 1972), tipo de solo (Ladd et al, 1981;Janns-Hammermeister et al, 1994) e forma de manejo (Wilson & Hargrove, 1986;Janzen & Radder, 1989), e inerentes aos adubos verdes (Palm & Sanchez, 1991;Smith & Sharpley, 1993), exercem grande influência sobre tais processos, devendo ser compreendidos e, na medida do possível, controlados para que otimizem os efeitos da adubação verde.…”
Section: Introductionunclassified
“…For instance, Salomonsson et al (1994) found that while bone meal applied to spring wheat just before stem extension increased grain protein to the same level as topdressed urea, slurry manure N was less available and had to be applied at planting to achieve a comparable increase in protein. The slower N availability from organic N sources may be exacerbated by the lack of soil incorporation with topdressing that could reduce N mineralization (Smith and Sharpley, 1993) or increase N volatilization losses (Cabrera et al, 1993). If true, incorporating organic N topdress sources with in‐season cultivation as is performed for weed management (Kolb and Gallandt, 2012) may increase N availability and subsequent plant uptake.…”
mentioning
confidence: 99%
“…Leaving previous crop residues near the soil surface, such as in NT, affects fertilizer N management for winter wheat (Westfall et al, 1996). Decomposing crop residues with wide C/N ratios can immobilize significant amounts of surface‐applied fertilizer N and/or slow mineralization of soil N (Rice and Smith, 1984; Knowles et al, 1993; Smith and Sharpley, 1993). Several researchers have reported lower wheat yields and a greater fertilizer N requirement for wheat planted after a high‐residue crop such as grain sorghum, compared with wheat planted after soybean, and have attributed much of those results to greater immobilization of N after grain sorghum (Hargrove et al, 1983; Sanford and Hairston, 1984; Staggenborg et al, 2003).…”
mentioning
confidence: 99%